Prognostic Value of the Geriatric Nutritional Risk Index in Non-Small Cell Lung Cancer Patients: A Systematic Review and Meta-Analysis - Wang, Haoyu; Li, Cui; Yang, Ruiyuan; Jin, Jing; Liu, Dan; Li, Weimin (Frontiers in Oncology, 2022)
Background Novel evidence showed that the Geriatric Nutritional Risk Index (GNRI) may lead to poor prognosis of human cancers. Therefore, we conducted a meta-analysis to explore the impact of GNRI in lung cancer and its prognostic value. Methods We searched the databases of PubMed, Web of Science, Embase, Scopus, and Cochrane Library up to July 2021 for relevant research and merged the hazard ratios (HRs) and 95% confidence intervals (CIs) to evaluate the association between GNRI and overall survival (OS), cancer-specific survival (CSS), and recurrence-free survival (RFS) in patients with lung cancer. Results Eight studies involving 2,399 patients were included in our primary meta-analysis. The results indicated that lower level of GNRI was associated with poorer OS, RFS, and CSS of lung cancer patients (OS: HR = 1.99, 95% CI: 1.68–2.35, p < 0.0001; RFS: HR = 2.34, 95% CI: 1.11–4.95, p = 0.0258; CSS: HR = 2.45, 95% CI: 1.43–4.18, p = 0.0011). The association was robust after subgroup analysis and sensitivity analysis. Conclusions GNRI may be a prognostic factor of lung cancer, which can lead to poorer survival. However, more prospective studies are necessary to confirm the results. Systematic Review Registration International Prospective Register of Systematic Reviews (PROSPERO), identifier CRD42021269574.